Dampak YouTube Shorts terhadap Pola Pikir dan Tingkah Laku Peserta Didik - Agil Syakhirotul Rizkiyah; Desy Safitri; Sujarwo (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2025)
The rapid advancement of digital technology has significantly transformed the way people interact, access information, and consume media. The internet, as the cornerstone of this transformation, enables instant access to information beyond the limits of space and time. One prominent manifestation of this progress is the rise of social media platforms, including YouTube Shorts, which offer short-form videos in an engaging and fast-paced format. This platform has gained immense popularity, not only among adults but also among children and adolescents. While YouTube Shorts can serve as a source of education and entertainment, its unrestricted access regardless of age raises serious concerns. Children are particularly vulnerable to exposure to content that is inappropriate for their psychological development, such as verbal violence, consumerist lifestyles, deviant behavior, and misleading information. This situation prompts a fundamental question: to what extent do digital broadcasts influence students’ mindset and behavior? This study employs a descriptive qualitative approach to explore the impact of YouTube Shorts consumption on students. The findings reveal a duality of influence: on one hand, appropriate content can enhance literacy, creativity, and language proficiency. On the other hand, without proper supervision, this platform may lead to addiction, weaken social interaction, and normalize behaviors that contradict educational values. Therefore, collaboration between parents and educators is essential. Active supervision at home and digital ethics education at school are crucial to shaping a generation that is both critical and wise in navigating the digital information landscape.